2020
DOI: 10.1175/jpo-d-19-0125.1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Shoaling Nonlinear Internal Bores across the Central California Inner Shelf

Abstract: We present observations of shoaling nonlinear internal bores off the coast of central California. The dataset includes 15 moorings deployed during September–October 2017 and cross-shore shipboard surveys. We describe the cross-shore structure and evolution of large-amplitude internal bores as they transit from 9 km (100-m depth) to 1 km offshore (10 m). We observe that two bores arrive each semidiurnal period, both propagating from the southwest; of the total, 72% are tracked to the 10-m isobath. The bore spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 50 publications
5
45
0
Order By: Relevance
“…The onshore propagating warm bore was at least 10 m thick with 0.2-3 m s −1 onshore velocities. These warm bores were similar to those seen around Oceano (McSweeney et al 2020b) and they propagate deep into the bay in the lee of Point Sal (not shown).…”
supporting
confidence: 73%
See 2 more Smart Citations
“…The onshore propagating warm bore was at least 10 m thick with 0.2-3 m s −1 onshore velocities. These warm bores were similar to those seen around Oceano (McSweeney et al 2020b) and they propagate deep into the bay in the lee of Point Sal (not shown).…”
supporting
confidence: 73%
“…Internal waves are important to the inner shelf over a range of time and spatial scales. Highly nonlinear internal tides and high-frequency internal waves occur in the inner shelf and are responsible for large changes in stratification and strong cross-shore currents over short time scales (Lee 1961;Cairns 1967;Winant 1974;Scotti and Pineda 2004;Sinnett et al 2018;McSweeney et al 2020b;Feddersen et al 2020), and also transport heat from the inner shelf to the surf zone (e.g., Sinnett and Feddersen 2019). These waves also transport plankton and nutrients across the inner shelf (Shanks and Wright 1987;Pineda 1991;Leichter et al 1998;Lennert-Cody and Franks 1999;Shroyer et al 2010); and can resuspend and transport sediment (Butman et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature observations versus 2017 yearday and height above the bed at M15 for the (a) total, (b) subtidal, (c) diurnal, and (d) semidiurnal frequency bands (seeFigure 1b). (e) Tidal elevations versus 2017 yearday (McSweeney et al, 2019)…”
mentioning
confidence: 99%
“…Both EOF modes 1 and 2 for ζ W are similar to those for ζ S in both vertical structure (not shown) and variance fraction (65% and 27%, respectively). The vertically smooth ζ / f means and low mode dominance of ζ / f variability indicates that the vorticity estimation method using 2 h filtered and cEOF reconstructed velocities (Section 2.2.1) is not noise contaminated due to aliasing of short scale variability associated with internal warm bores or solitons (Colosi et al., 2018; McSweeney et al., 2020) that likely have contributions at cEOF mode 2. If noise were significant, one would expect small‐scale vertical variation in the statistics due to estimation error.…”
Section: Spatial Structure and Temporal Variability Of Vorticity Estimentioning
confidence: 98%